2003
DOI: 10.1126/science.1082142
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid Modulation of Immune Function and Sexual Attractiveness in Zebra Finches

Abstract: One hypothesis for why females in many animal species frequently prefer to mate with the most elaborately ornamented males predicts that availability of carotenoid pigments is a potentially limiting factor for both ornament expression and immune function. An implicit assumption of this hypothesis is that males that can afford to produce more elaborate carotenoid-dependent displays must be healthier individuals with superior immunocompetence. However, whether variation in circulating carotenoid levels causes va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
550
9

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 581 publications
(582 citation statements)
references
References 24 publications
23
550
9
Order By: Relevance
“…Recent experimental studies have confirmed that males with greater access to carotenoids have more colourful ornamental displays, better antioxidant defences and can mount larger immune responses (e.g. Blount et al 2003;McGraw & Ardia 2003;Kolluru et al 2006;Kurtz et al 2006; but see Navara & Hill 2003). However, evidence of a link between carotenoid supply and adult survival has so far been correlational (Hill 1991;Hõrak et al 2001) and no previous study has explicitly tested how carotenoid supply may influence resistance to senescence or longevity, and how these competing demands affect their ability to allocate carotenoids to sexual signals.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental studies have confirmed that males with greater access to carotenoids have more colourful ornamental displays, better antioxidant defences and can mount larger immune responses (e.g. Blount et al 2003;McGraw & Ardia 2003;Kolluru et al 2006;Kurtz et al 2006; but see Navara & Hill 2003). However, evidence of a link between carotenoid supply and adult survival has so far been correlational (Hill 1991;Hõrak et al 2001) and no previous study has explicitly tested how carotenoid supply may influence resistance to senescence or longevity, and how these competing demands affect their ability to allocate carotenoids to sexual signals.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, if the overall quality of a feather is low, then the white tip will wear off faster revealing the lower feather quality ( Fitzpatrick 1998;Kose & Møller 1999). Experimental studies on wild animals linking aspects of individual quality to ornament variation are still scarce, but for captive birds two recent studies on males in zebra finches and blackbirds have shown that manipulating immune function leads to rapid changes in bill colour (Blount et al 2003;Faivre et al 2003). In a previous observational study, we found that the size of the white fringes in the wing feathers of female common eiders correlated with previously experienced reproductive costs and immune function .…”
Section: Introductionmentioning
confidence: 99%
“…(c) Laboratory analyses of antioxidants Antioxidants in plasma, liver and egg yolk were assessed by HPLC-based methods described earlier (Surai et al 2001a;Blount et al 2003). In brief, 15-30 ml of plasma was vortexed with an equal volume of 5% sodium chloride, plus two volumes of ethanol, 500 ml hexane was then added and vortexed.…”
Section: (B) Field Proceduresmentioning
confidence: 99%